Multidrug Resistance and the Lung Resistance-Related Protein in Human Colon Carcinoma SW-620 Cells - Masaki Kitazono; Tomoyuki Sumizawa; Yuji Takebayashi; Zhe‐Sheng Chen; Tatsuhiko Furukawa; Satoshi Nagayama; Akira Tani; Sonshin Takao; Takashi Aikou; Shin-ichi Akiyama (1999)
Lung resistance-related protein (LRP), the major vault protein in humans, is sometimes overexpressed in multidrug-resistant cells. Because cells transfected with the LRP gene did not express the multidrug-resistant phenotype, we investigated whether LRP is involved in multidrug resistance.SW-620 cells, a human colon carcinoma cell line, alone or transfected with an expression vector carrying a LRP-specific ribozyme or with an empty vector, were treated with sodium butyrate to induce differentiation. Expression of P-glycoprotein, multidrug resistance protein, and LRP in the cells was examined by northern and western blotting, and the efflux of doxorubicin in the cells or isolated nuclei was examined by fluorescence microscopy.A 2-week treatment with sodium butyrate induced LRP and conferred resistance to doxorubicin, vincristine, etoposide, gramicidin D, and paclitaxel (Taxol) in SW-620 cells. Insertion of either of two LRP-specific ribozymes into SW-620 cells inhibited these activities. Levels of drugs accumulating in the cells were not decreased by sodium butyrate, suggesting that the adenosine triphosphate-binding cassette transporter is not involved in sodium butyrate-induced multidrug resistance. Doxorubicin was mainly located in the nuclei of untreated cells and in the cytoplasm of sodium butyrate-treated cells. Isolated nuclei from untreated cells or sodium butyrate-treated cells incubated with anti-LRP polyclonal antibodies contained more doxorubicin than the nuclei of sodium butyrate-treated cells alone. Efflux of doxorubicin was greater from the nuclei of sodium butyrate-treated cells than the nuclei of untreated cells or of sodium butyrate-treated cells transfected with a LRP-specific ribozyme and was inhibited by an anti-LRP polyclonal antibody.LRP is involved in resistance to doxorubicin, vincristine, etoposide, paclitaxel, and gramicidin D and has an important role in the transport of doxorubicin from the nucleus to the cytoplasm.